Stolen secrets - Jenkins, Jerry B.; Fabry, Chris, 1961- (Carol Stream, Ill. : Tyndale House, 2005)
The quiet community of Red Rock is upset by an apparent abduction attempt on two middle school girls.
4.4
3-6
Keywords: Christian life -- Juvenile fiction; Families -- Juvenile fiction; Honesty -- Juvenile fiction; Kidnapping -- Juvenile fiction; Twins -- Juvenile fiction; Christian life -- Fiction; Family life -- Fiction; Honesty -- Fiction; Kidnapping -- Fiction; Mystery and detective stories; Twins -- Fiction; Christian fiction; Christian life -- Fiction; Family life -- Fiction; Honesty -- Fiction; Kidnapping -- Fiction; Mystery fiction; Twins -- Fiction; Christian fiction; Mystery fiction